THE NEW TREATY: RUSSIA AND EUROPEAN UNION PIT AGAINST EACH OTHER AGAIN - A. Klyomin (Russian Journal of Economics and Law)
The article studies the new treaty between the Russian Federation and European Union on the agreement to begin the work on the partnership and cooperation treaty - the act confirming the achieved economic and military-political status quo of the parties and the beginning of the new stage in the historic confrontation of Russia and the West.